Immune mediated neuropathies in pregnancy and postpartum period - Reza Boostani; Fariba Zemorshidi; Bahareh Foghanian (Mashhad University of Medical Sciences, 2021)
Introduction: Gillian- Barre- Syndrome (GBS) and Chronic Inflammatory Demyelinating Polyradiculoneuropathy (CIDP) are immune-mediated disorders of peripheral nervous system which presented with progressive symmetrical muscle weakness, deep tendon reflexes and sensory symptoms. This review study was performed with aim to investigate the effects of pregnancy and postpartum period on immune mediated neuropathies and also the effects of these neuropathies on the prognosis of pregnancy and treatment of these diseases during this period. GBS evolves acutely in 2 to 4 weeks and in two third of cases, there is a history of viral or bacterial infections before the onset of symptoms. CIDP is a chronic auto-immune disorder that progresses at least for 8 weeks in comparison to GBS that evolves in 4 weeks. In this article, we reviewed the effects of pregnancy and postpartum period on these diseases as well as the effects of GBS and CIDP on pregnancy and postpartum period in different articles performed in recent years and collected the appropriate treatments of these disorders during the pregnancy and postpartum period. This article could be a proper guideline for neurologists and obstetrics and gynecologists to treat and predict the prognosis of mothers with immune-mediated neuropathies.  Conclusion: Many immune mediated neuromuscular disorders occur in women at childbearing ages. Incidences of these disorders may affect the pregnancy and childbirth. Also, pregnancy may have influences in the symptoms and treatment of the mentioned disorders. GBS and CIDP are among the most important immune-mediated peripheral nervous system disorders. Recognizing the effects of GBS and CIDP during pregnancy and postpartum period and the effects of pregnancy on the process of these two disorders is so important.